Translating Inter-country Adoption as Transcultural Communication - Bhattarai, Achyutananda (BMC Research Journal, 2024)
This article attempts to explore transcultural communication through the translated version of “Inter-country Adoption” of the National Civil Code, 2017 ( the Muluki Dewani Samhita) Ain, 2074 BS). It observes the “Hague Adoption Convention, 1993” principles and the Manu’s idea of dharmaputra (adopted sob) mentioned in the “Manusmriti”, the law of Hindu, and its influence on the formation of adoption law in Nepal. The primary purpose of Nepali legal translation is to transfer Nepali legal culture for global communication. The cultural theory of translation developed by Lawrence Venuti and Marry Snell-Hornby and the equivalence theory of Eugene Nida and Peter Newmark are were used as the theoretical base for the study. The significance of this study is to the parents waiting for inter-country adoption and to the university students who have taken translation studies as their major subject. This article concludes that legal translation in Nepal is a strategy to deliver Nepali legal culture to the globe and vice versa.